2017
DOI: 10.18869/nirp.jmr.10.4.177
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Neurofeedback Training on Reading and Spelling Skills of 8 to 12 Years Old Children With Dyslexia

Abstract: Introduction: Progress in understanding dyslexia has led to the discovery of abnormal brain waves in the areas related to reading skill. It seems that improving the function of these areas by regulating their waves is helpful for reading process. This study aimed to investigate the efficacy of neurofeedback training (NFT) in improving children's reading difficulties. Material and Methods:This was a single-subject experiment with A-B-A design. Four dyslexic boys (age range 8-12 years) received twenty 30-minute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…According to the authors, these kinds of changes could indicate integration of sensory and motor areas that could explain the behavioral advantage. This approach was also applied by Raesi et al (2017), who found significant improvements in accuracy, comprehension, and spelling after the training.…”
Section: Dyslexia and Neurofeedbackmentioning
confidence: 99%
“…According to the authors, these kinds of changes could indicate integration of sensory and motor areas that could explain the behavioral advantage. This approach was also applied by Raesi et al (2017), who found significant improvements in accuracy, comprehension, and spelling after the training.…”
Section: Dyslexia and Neurofeedbackmentioning
confidence: 99%